Suitability Analysis as a Recommendation System for Housing Search - Puri, Jaskaran Singh (2022)
Puri, J. S., & Cabral, P. (2022). Suitability Analysis as a Recommendation System for Housing Search. In C. Grueau, & L. Ragia (Eds.), Proceedings of the 8th International Conference on Geographical Information Systems Theory, Applications and Management: GISTAM 2022 (Vol. I, pp. 91-98). SciTePress - Science and Technology Publications. https://doi.org/10.5220/0011014700003185-----This study was supported by national funds through FCT (Fundação para a Ciência e a Tecnologia) under the project UIDB/04152/2020 - Centro de Investigação em Gestão de Informação (MagIC).